Mechanisms and consequences of widespread random monoallelic expression - Chess, Andrew (Nature reviews. Genetics, 2012)
Key Points Monoallelic expression is an interesting epigenetic phenomenon, as it requires cells to treat the two alleles of a gene unequally, even though their sequences can be identical and they are present in the same nucleus. Although monoallelic expression in the context of genomic imprinting is governed by marks placed during gametogenesis, for random monoallelic expression the determination of which allele will be expressed must be made by individual cells in the developing embryo. After a choice has been made, descendent cells maintain the choice. It has been known for decades that the entire X chromosome in the cells of female placental mammals is subject to random monoallelic expression, but until recently autosomal examples were thought to be restricted to the immune system and chemosensory systems. Genome-scale analyses have now uncovered an unexpectedly large number of autosomal genes that are subject to random monoallelic expression and have shown that these genes encode proteins with a wide range of functions. A number of unusual mechanisms are known to be involved in the regulation of some of these genes, but for most monoallelically expressed genes the mechanisms remain to be defined. Random monoallelic expression has the potential to affect the connection between genotype and phenotype and also has the potential to affect natural selection and the evolution of gene families. A suprisingly large proportion of mammalian genes are now known to be subject to random monoallelic expression. This Review discusses our latest understanding of the underlying mechanisms and of the implications for cellular functions and organismal evolution. Although random monoallelic expression has been known for decades to affect genes on the X chromosome in female placental mammals, until a few years ago it was thought that there were few autosomal genes that were regulated in this manner. New tools for assaying gene expression genome-wide are now revealing that there are perhaps more genes that are subject to random monoallelic expression on mammalian autosomes than there are on the X chromosome and that these expression properties are achieved by diverse molecular mechanisms. This mode of expression has the potential to have an impact on natural selection and on the evolution of gene families.